Metastatic Neuroendocrine Tumors to the Breast: Diagnostic Pitfall With Significant Clinical Implications. Issue 5 (September 2017) - Clark, Beth Z.; Bhargava, Rohit
Abstract : Abstract: Two cases of metastatic neuroendocrine tumors to the breast are reported. Both patients had previously received a diagnosis of and treated for ileal neuroendocrine tumors. One case had an initial diagnosis of invasive ductal carcinoma. This report includes review of pertinent medical literature and differential diagnosis, along with discussion of preferred immunohistochemical stains for establishing the diagnosis of a metastatic lesion rather than a primary breast neoplasm. Suspicion for metastasis must be high in breast tumors with morphologic features of neuroendocrine differentiation and in low-grade non–gland-forming tumors that are estrogen receptor, progesterone receptor, and Her-2/neu negative, as a metastasis to the breast was the presenting sign of a neuroendocrine tumor elsewhere in the body in nearly one-third of the reported cases. Treatment for a metastatic lesion may be significantly different from treatment of a primary breast tumor in that radiation therapy to the breast and lymph node sampling may not be indicated, and systemic therapies will likely be considered if the correct diagnosis can be made.